2022
DOI: 10.1128/spectrum.01178-22
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Mycobacterium tuberculosis-Specific and Nonspecific Immune Responses in Women with Tuberculosis Infection during Pregnancy

Abstract: Tuberculosis (TB) is globally one of the most common causes of death, and a quarter of the world's population is estimated to have TB infection. The risk of active TB is increased in connection to pregnancy, a phenomenon that could be due to physiological immune changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The elevated incidence of TB disease in connection to pregnancy observed in low-endemic countries is likely to be due to pregnancy-induced progression of TBI [ 13 , 14 ]. Furthermore, we and other researchers have found altered M. tuberculosis –specific immune responses during pregnancy [ 17 , 20 , 30 , 31 ], suggesting that the host–pathogen interaction changes during pregnancy [ 17 , 20 ].This register-based study was not designed to investigate mechanisms involved in these phenomena. Yet, we speculate that low-grade inflammation triggered by TBI during pregnancy might be involved in the association between TBI and pregnancy complications observed in our study population [ 26 , 27 , 32 ].…”
Section: Discussionmentioning
confidence: 70%
“…The elevated incidence of TB disease in connection to pregnancy observed in low-endemic countries is likely to be due to pregnancy-induced progression of TBI [ 13 , 14 ]. Furthermore, we and other researchers have found altered M. tuberculosis –specific immune responses during pregnancy [ 17 , 20 , 30 , 31 ], suggesting that the host–pathogen interaction changes during pregnancy [ 17 , 20 ].This register-based study was not designed to investigate mechanisms involved in these phenomena. Yet, we speculate that low-grade inflammation triggered by TBI during pregnancy might be involved in the association between TBI and pregnancy complications observed in our study population [ 26 , 27 , 32 ].…”
Section: Discussionmentioning
confidence: 70%
“…Interestingly, most TB cases in previous studies were reported postpartum [ 11 , 12 ], whereas the majority of people with TB disease in our study had been diagnosed during pregnancy. Pregnancy confers physiological immune changes, which may increase the risk of progression of TBI [ 32 , 33 ]. These immune modifications are restored shortly after delivery.…”
Section: Discussionmentioning
confidence: 99%